Transcriptome analysis of Porphyromonas gingivalis and Acinetobacter baumannii in polymicrobial communities. (3rd August 2018) - Miller, D.P.; Wang, Q.; Weinberg, A.; Lamont, R.J.
Summary: Acinetobacter baumannii is a nosocomial, opportunistic pathogen that causes several serious conditions including meningitis, septicemia, endocarditis, and pneumonia. It can be found in the oral biofilm, which may be a reservoir for pneumonia and chronic obstructive pulmonary disease. Subgingival colonization by A. baumannii is associated with chronic and aggressive periodontitis as well as refractory periodontal disease. Porphyromonas gingivalis, a keystone periodontal pathogen localized to subgingival plaque, is also implicated in several chronic conditions including aspiration pneumonia. Although both bacteria are found together in subgingival plaque and can cause multiple polymicrobial infections, nothing is known about the interactions between these two important human pathogens. In this study, we used RNA sequencing to understand the transcriptional response of both species as they adapt to heterotypic communities. Among the differentially regulated genes were those encoding a number of important virulence factors for both species including adhesion, biofilm formation, and protein secretion. Additionally, the presence of A. baumannii increased the abundance of P. gingivalis in model dual‐species communities. Collectively these results suggest that both P. gingivalis and A. baumannii adapt to each other and have synergistic potential for increased pathogenicity. In identifying the mechanisms that promote pathogenicity and refractory disease, novel approaches to mitigate polymicrobial synergistic interactions may be developed to treat or prevent associated diseases.